Relative Change in NT-proBNP Level: An Important Risk Predictor of Cardiovascular Congestion in Haemodialysis Patients - M. Pastural-Thaunat (Nephron Extra, 2012)
Background: Cross-sectional studies have shown that B-type natriuretic peptide (BNP) and its N-terminal fragment (NT-proBNP) are predictive of cardiovascular death in haemodialysis (HD) patients. In the present study, we tested the hypothesis that monitoring NT-proBNP measurements adds further prognostic information, i.e. predicts congestive heart failure (CHF) events. Methods: In a prospective cohort of 236 HD patients, NT-proBNP levels were measured monthly during 18 months. Patients were divided according to the occurrence of CHF events. In a nested case-control study, we assessed the evolution of NT-proBNP levels. Results: On average, the 236 HD patients were followed up for 12.5 months, a period during which 44 patients developed a CHF event (half requiring hospitalisation). At baseline, patients who developed a CHF event had significantly more dilated cardiomyopathy and/or altered left ventricular ejection fraction and higher NT-proBNP levels compared with patients who did not develop a CHF event. During follow-up, we observed a significant increase in NT-proBNP levels preceding the CHF event. At a 20% relative increase of NT-proBNP, the sensitivity of NT-proBNP as a predictor of CHF events was 0.57 and the specificity 0.77. Conclusion: The relative change in NT-proBNP levels is a significant risk predictor of a CHF event.